Marine fish farming in Italy - Landoli C. (Mediterranean offshore mariculture, 2000)
Expansion of Italian aquaculture in brackish waters has mainly occurred during the last two decades, and was preceded by the development of fresh-water aquaculture. At present, Italian aquaculture, with a tonnage of about 40 per cent of the fish catch, appears in line with key international trends. Italian fish culture production mainly follows two technologies: productive management of the coastal environment (mostly lagoons), performed principally in marine and brackish water using extensive and semi-intensive techniques, and the intensive farming of highly valuable species, carried out mostly in tanks and cages. In recent years Italian aquaculture has been characterized by a strong increase in output due to the technological optimization of existing installations as well as to the application of innovative technology and the setting up of new facilities; in 1997 the total production of marine species reached 14,700 MT.
Advanced Course of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Mediterranean Offshore Mariculture', 1997/10/20-24, Zaragoza (Spain)